2015
DOI: 10.1038/srep11873
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide-Based Silver Nanoparticle-Containing Composite Hydrogel as Highly Efficient Dye Catalysts for Wastewater Treatment

Abstract: New reduced graphene oxide-based silver nanoparticle-containing composite hydrogels were successfully prepared in situ through the simultaneous reduction of GO and noble metal precursors within the GO gel matrix. The as-formed hydrogels are composed of a network structure of cross-linked nanosheets. The reported method is based on the in situ co-reduction of GO and silver acetate within the hydrogel matrix to form RGO-based composite gel. The stabilization of silver nanoparticles was also achieved simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(81 citation statements)
references
References 59 publications
7
74
0
Order By: Relevance
“…The C=O stretch for rGO further confirmed the interaction of the rGO with the polymer in the hydrogel network. Some researchers reported similar findings for hydrogels containing rGO [16,17]. The absence of the NH 2 stretching which was conspicuous in pure acrylamide in the GW1-GW4 hydrogel further confirmed the successful crosslinking of acrylamide (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The C=O stretch for rGO further confirmed the interaction of the rGO with the polymer in the hydrogel network. Some researchers reported similar findings for hydrogels containing rGO [16,17]. The absence of the NH 2 stretching which was conspicuous in pure acrylamide in the GW1-GW4 hydrogel further confirmed the successful crosslinking of acrylamide (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…This observation suggested that the hydrogels enhanced the thermal stability of the drugs which is attributed to the high degree of crosslinking of the hydrogel and interaction between rGO and the polymeric network (Fig. 6b) [17].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In recent years, nanocomposite hydrogels have been widely used in various application (Bergaya et al, 2013;Jiao et al, 2015Jiao et al, , 2016Liu et al, 2010;Thakur et al, 2016). Nanocomposite hydrogels are three-dimensional networks of hydrophilic polymers that can absorb and maintain a large quantity of water in the presence of nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, graphene oxide (GO) and reduced graphene oxide (rGO) became a hot topic and opened an entirely new domain in the area of material science [1][2][3]. The opportunity to combine GO with inorganic nanoparticles, thereby forming graphene-nanoparticle hybrid structures, is currently of interest for applications in bioelectronics, energy production, biomedicine, and environmental remediation [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%